PROBLEMS AND PROSPECTS OF APPLICATION OF STRATEGIES OF PERSONNEL MANAGEMENT OF INTERNATIONAL COMPANIES IN UKRAINIAN BUSINESS PRACTICE - Ptashchеnko, O.; Chernobay, L.; Malykhina, S.; Verezomska, I.; Yaremchuk, S. (My University, 2022)
The article examines the impact of staff on the successful operation of the enterprise in the long run. Companies need to consider the attitudes, values, expectations, perceptions and typical behaviors of workers from different cultures. The success of companies in the global market is increasingly determined by whether they have managed to create an effective system of personnel management to eliminate friction in relations between employees of different nationalities and with different cultural traditions. When estimating the exact contribution of both an individual employee and the team as a whole, the end result of an international company’s business is a complex process, because in addition to direct labor costs, the product is also invested in fixed and current assets. Today, HR specialists need to meet the needs of employers in the context of new professionals, in particular, training manager, HR specialist, HR manager, HR director, team manager, sales coach, headhunter, corporate culture manager and others. The global changes and their consequences in the field of HR-management are identified: informatization, spread of digital technologies, aging of knowledge and technologies, national demographic changes, lack of qualified personnel, individualization, uncertainty in global, regional, and national markets, emphasis on sciences such as psychology and sociology. The cultural, economic, social and political differences of an international company have a significant impact on the formation of management styles and the adaptation and functioning of staff in the host country. Problems of personnel management strategies of international companies in Ukrainian business practice are highlighted: style and practice of company management, socio-cultural factors, differences in wages and working conditions, labor movement problems, relationship factor, control factor and contradictions. The advantages of personnel management strategies of international companies in Ukrainian business practice are studied: trainings for personnel, digitalization at enterprises, observance of current legislation, ensuring objective assessment of personnel competencies, development of corporate culture among enterprise personnel.
ПРОБЛЕМИ I ПЕРСПЕКТИВИ ЗАСТОСУВАННЯ СТРАТЕГІЙ УПРАВЛІННЯ ПЕРСОНАЛОМ МІЖНАРОДНИХ КОМПАНІЙ В УКРАЇНСЬКІЙ БІЗНЕС-ПРАКТИЦІ
Keywords: strategy; personnel; enterprise; increase; development; stimulation; management